Housing and Support Narratives of People Experiencing Mental Health Issues: Making My Place, My Home - Fossey, Ellie; Harvey, Carol; McDermott, Fiona (Frontiers in Psychiatry, 2020)
Background: Choice, control, privacy and security are widely reported housing preferences of mental health consumers; are associated with improved well-being, greater housing satisfaction, and important for recovery. This paper describes housing and neighbourhood experiences from a larger qualitative study that sought to learn with people experiencing mental health issues about their everyday lives in an Australian urban community. Methods: A participatory approach to health research informed this study. A participatory reference group of four people with consumer perspective knowledge and experience of mental health issues and four mental health practitioners with service provider and researcher perspectives worked together over a four-year period. Participants were 18 women and 21 men with ongoing mental health issues living in metropolitan Melbourne, and in receipt of community mental health care. Participants each took part in a focus group or 1-3 interviews, subsequently analysed using narrative and thematic analytic strategies, underpinned by reflective discussions in the participatory reference group. Findings: Participants’ experiences of their housing and neighbourhoods emphasized qualities that either contributed to or challenged their sense of being ‘at home’. Identifying with a place as home was transformative, especially when supported by friendly neighbourhood interactions, safety and accessibility of local amenities. Unsatisfactory housing situations and limited income worked against participants’ efforts to regain a sense of wellbeing and improve their situations. When being home was challenging, strategies used to counteract this included getting a pet and getting out as a means of resisting isolation at home. Differing views and ways of using the available support workers were described, suggesting tensions between seeking to be self-sufficient and valuing support. Conclusions: Social housing locations and housing-related support should explicitly attend to safety and security concerns. Collaborative care planning and outreach support should attend to supports for navigating issues with neighbours, housing, harnessing natural supports and opportunities for being in others’ company, as well as recognizing the importance of pets in people’s lives. Understanding the strategies that mental health consumers find helpful in creating a sense of being at home, and the role of ‘place’ in recovery merit further consideration in research and practice.